India as a Net Security Provider in South Asia: Challenges, Opportunities, and Geopolitical Dynamics - Tuan Thang, Ngo; My Hai Loc, Tran (Journal of Strategic and Global Studies, 2025)
India’s emergence as a net security provider in South Asia is a significant development, driven by its strategic interests and the region's shifting geopolitical landscape. This paper explores the challenges, opportunities, and broader geopolitical dynamics that shape India’s security policies and initiatives in South Asia. Through qualitative research and the lens of structural realism, the study assesses India's efforts to maintain regional stability, counter terrorism, and address security threats in its immediate neighborhood, including Bangladesh, Nepal, Sri Lanka, Bhutan, and the Maldives. The analysis delves into the complexities posed by India’s traditional rivalries with Pakistan and China, highlighting how these relationships influence regional security management. Despite its growing military power in the Indian Ocean, India’s aspirations for regional leadership face hurdles. The study identifies key challenges, such as slow progress in developing deeper security ties with other Indian Ocean countries and the increasing expectation from regional actors for India to lead collaboratively. While India has the potential to assert itself as a major security provider, its reluctance to engage more proactively with key players in the region may hinder its influence. The study concludes by arguing that India must prioritize building stronger, cooperative security partnerships to solidify its leadership role in South Asia. By doing so, India can enhance regional stability and extend its strategic reach, ensuring a balance between its national security interests and its regional responsibilities.